2017
DOI: 10.1002/apj.2073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microstructure design on aluminum surface hydrophobic and ice‐retarding properties

Abstract: The poor mechanical strength of superhydrophobic surface limits its use in civil aviation. In this work, superhydrophobic surfaces with open and closed microstructure design were prepared, and their hydrophobicity and icephobicity over icing/de-icing cycles were thoroughly studied. For all samples, contact angle decreased and contact angle hysteresis increased over time. However, surface with interconnected hollow honeycomb microstructure design kept its Cassie-Baxter state even after 20 times icing/de-icing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…In fact, carbon-rich molecules can be absorbed from the ambient air, and the surface chemistry can be accordingly changed [ 31 , 32 ], making the wetting behavior time-dependent and its functionality limited for practical applications [ 33 ]. Moreover, microstructures fabricated on aluminum with surface features in the range of 30 to 50 µm have shown ice-delaying properties for single droplets freezing on the surface [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, carbon-rich molecules can be absorbed from the ambient air, and the surface chemistry can be accordingly changed [ 31 , 32 ], making the wetting behavior time-dependent and its functionality limited for practical applications [ 33 ]. Moreover, microstructures fabricated on aluminum with surface features in the range of 30 to 50 µm have shown ice-delaying properties for single droplets freezing on the surface [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, using regular and repetitive patterns it was possible to produce surfaces presenting air-cushion like behaviour resulting in lower adhesion and thus leading water droplets to easy roll at the materials’ surface (rolling-off phenomena) 13 . In particular, triangular-like patterns were fabricated on aluminium using photolithography methods, obtaining both hydrophobic and ice-retarding characteristics 14 . In addition, it was also reported that micro/nano-rough aluminium surfaces showing hydrophobic properties can reduce the anti-icing behaviour and thus forming ice even faster 15 .…”
Section: Introductionmentioning
confidence: 99%
“…As a proof experiment, by using hydrothermal method, X . K. Zhang respectively obtained the Zn–Al LDH (Layered Double Hydroxide) superhydrophobic films with layer–shaped nanowalls and interconnected hollow structure (static water APCA up to 161.39°, SA< 10°) [19], as well as the Bayerite/Zn–Al LDH superhydrophobic films with micro/nano composite structure (static water CA up to 167.32°, SA < 3°), respectively in molarity rate of NH 3 H 2 O/Zn 2+ of 0.75:1 and 1.25:1 (Fig. 7).…”
Section: Methods Detailsmentioning
confidence: 99%